The Influence of Entrepreneurship Education on Students Entrepreneurial Interest: A Case Study of Technopreneurship and Innovation Courses - Sari, Ulan Purnama (Journal of Engineering Education and Pedagogy, 2024)
The lack of job opportunities and the focus of higher education institutions on producing graduates as job seekers rather than creating job opportunities are the causes of high unemployment rates among educated individuals, including students. Therefore, the government is striving to increase the number of entrepreneurs through entrepreneurship education in higher education institutions, including the Department of Building Engineering Education at Universitas Negeri Jakarta, to enhance their interest in entrepreneurship so they can assist the government in reducing unemployment rates. This thesis aims to examine the influence of entrepreneurship knowledge gained from the technopreneurship and innovation course on the entrepreneurial interest of Building Engineering Education students at Universitas Negeri Jakarta. The data analysis technique used is simple regression analysis employing quantitative calculation methods such as normality tests, heteroscedasticity tests, and hypothesis testing, including regression equation testing, coefficient of determination testing, and t-tests. Data collection techniques in this research include multiple-choice tests and questionnaires with a total of 58 student respondents. The research findings indicate a positive and significant influence of the Entrepreneurship Knowledge variable in the Technopreneurship and Innovation Course on Entrepreneurial Interest. The regression result is Y = 12.608 + 0.436X, with a calculated t-count of 13.861 > the tabulated t-table of 2.002 (for df 56) and a significance value of 0.000 < 0.05, indicating significance. The coefficient of determination 〖(R〗^2) is 73.9%. Thus, it is concluded that Entrepreneurship Knowledge in the Technopreneurship and Innovation Course has a positive and significant influence on Entrepreneurial Interest.